The Analysis of Subtitle Strategies in "cin(T)a", an Indonesian Indie Film - Sardiyana, Dea (2015)
This research is entitled "The Analysis of Subtitle Strategies in cin(T)a, an Indonesian Indie Film." This research investigates the subtitle strategies that are used in the film and to know the quality of subtitling in the English subtitle of the film cin(T)a (2009) directed by Sammaria Simanjuntak. A descriptive qualitative research method is used to to explain, analyze, and classify data through various techniques, such as examining documents and interviewing participants (Creswell 2009, p.175). The research reveals that there are 575 dialogues to be analyzed in this film. The data are analyzed by applying subtitle strategies theory proposed by Gottlieb (1992). In this research, there are nine subtitle strategies used by the translator; they are transfer, paraphrase, imitation, expansion, condensation, transcription, deletion, decimation, and resignation.It is also found that there are three dominant strategies. They are transfer, paraphrase, and imitation. Transfer as the most frequent strategy occurs 368 items or covers 64% of the data. It is followed by the other strategy; expansion, condensation, transcription, deletion, decimation, and resignation. Transfer is the most frequent strategy. This is because the subtitler translated the source language (SL) accurately and completely without leaving any single word. Then, they do not need additional information or deletion to give the same effect as the source language (SL). The possible reason why this strategy is used is because he or she does not want to lose the original meaning of the source language. In addition, based on the criteria for the judgement of translation quality proposed by Barnwell (1996), the quality of subtitle in the English subtitles of the film cin(T)a is in grade 3 or in "good" level. The criteria for the judgement of translation quality are based on accuracy, clarity, and naturalness by the judgement of two people. These two people are native speakers. This shows that transfer strategy is appropriate to apply in the subtitle of this film.